Visual rating and volumetry of the medial temporal lobe on magnetic resonance imaging in dementia: a comparative study. Issue 5 (1st November 2000) - Wahlund, Lars-Olof; Julin, Per; Johansson, Sven-Erik; Scheltens, Philip
Abstract : OBJECTIVES: It has been shown that atrophy of medial temporal lobe structures such as the hippocampus and entorhinal cortex shown on MRI may distinguish patients with Alzheimer's disease from healthy controls. However, the diagnostic value of visual inspection and volumetry of medial temporal lobe atrophy (MTA) on MRI in a clinical setting is insufficiently known. METHODS: Medial temporal lobe atrophy in 143 patients was visually rated from hard copies, using a 0–4 rating scale and a comparison was made with the volumes (cm 3 ) of the medial temporal lobe as estimated with volumetry, using a stereological method. All patients were recruited in an unselected way in a clinical setting in the centre for memory impairments at the Huddinge University Hospital. Patients with Alzheimer's disease (n=41), patients with other dementias (vascular dementia, frontotemporal dementia, and unspecified dementia; n=36) as well as non-demented subjects (n=66) were included. Medial temporal atrophy and volumetry were evaluated as a diagnostic tool by performing logistic regression analysis including age, sex, and mini mental state examination (MMSE) score and calculating the sensitivity and specificity and percentage correct classification. RESULTS: Visual and volumetric analysis yielded statistically significant differences between patients with Alzheimer's disease and non-demented subjects, as well as between those with other dementias and non-demented subjects. Combining MMSE scores and visually rated MTA ratings yielded a sensitivity of 95% for Alzheimer's disease, 85% for other dementias. Non-demented subjects were identified with a specificity of 96%. Volumetry did not have an added value over the MMSE score alone. CONCLUSIONS: Visual rating of MTA is a clinically useful method for differentiating Alzheimer's disease from controls and is both quicker and more accurate than volumetry.